Implementation of Prognostics and Health Management in South Korean Defense Systems - Park, Jaehun; Kim, Yong Soo; Bae, Suk Joo; Kim, Sung Kyu; Lee, Mi Lim; Sung, Si-Il (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
As an advanced reliability-estimation concept, prognostics and health management (PHM) has been widely used to estimate the remaining useful life of individual systems, especially those embedded in U.S. military applications. However, there have as yet been no specific attempts to apply PHM or another advanced reliability-estimation methods to South Korea’s defense systems. We herein examine a feasible application to improve the reliability, availability and maintainability (RAM) of defense system performance, mainly through simulation-study-based comparison of South Korean and United States reliability-estimation technologies and strategies. We then provide a long-term-perspective roadmap for the introduction ofPHM to South Korea’s defense systems. In particular, it is expected that availability improvement in South Korean defense systems can be achieved through accurate residual-life prediction by introducing PHM to defense system operation.